SOME TIPS ON THE IMPORTANCE OF CREATIVE WRITING IN LANGUAGE CLASSES - Elmuratova, A.S. (FAN va JAMIYAT, 2018)
The article is devoted to the description of peculiarities of writing. The author of the article also studies different methods of teaching writing and gives recommendations for improving writing, and creative writing, in particular. There were analyzed the potential possibilities of creative writing in teaching a foreign language.